Produk Kreasi Tali Kur sebagai Sarana Peningkatan Produktifitas Ibu Rumah Tangga - Fitri Dwi Indarti; Ratna Hardianningrum; Meilinda Dewi Astuti; Clarisa Isnaini Aulia Dewi (Jurnal Surya Masyarakat, 2024)
The Community Association 02 area of Kelurahan Gisikdrono has 1,097 residents with 353 households. The number of female residents is 531 people, most of whom are housewives who work at home and are active in PKK activities. Through the PKK movement, housewives can strengthen the family to improve welfare. One of the reasons women work is to support the family economy. The weakness of the family economy makes housewives involved in increasing family income by looking for additional income by working for wages. In the context of efforts to improve the family economy, housewives must improve their ability to help the family economy. Given this condition, the service team tried to encourage housewives who have a lot of unproductive time in RW 02 Gisikdrono Village to be creative to make products that have economic value. She is supported again by the Waste Bank activities that have long been carried out by housewives in RW 02 Gisikdrono Village. This macrame art can be an alternative for housewives of Community Association 02 Gisikdrono Village in producing bags, wallets, key chains, brooches, etc. to get a high selling value of goods by combining the utilization of used goods in Waste Bank activities.